AgNPs embedded N- doped highly porous carbon derived from chitosan based hydrogel as catalysts for the reduction of 4-nitrophenol. (15th September 2019) - Alhokbany, Norah; Ahama, Tansir; Ruksana,; Naushad, Mu; Alshehri, Saad M.
Abstract: The fabrication of AgNPs into the N-doped carbon matrix with uniform dispersion and a strongly coupling interface is one of the main strategies to improve the catalytic activity of nanocomposite. Here, highly porous AgNPs embedded into the N-doped carbon (Ag/N–C) nanocomposite was fabricated using chitosan based hydrogel. The fabricated Ag/N–C was characterized using various analytical techniques (including SEM, TEM, XRD, BET, TGA and FT-IR, Ramman and XPS). The as-synthesized Ag/N–C nanocomposite with high specific surface area (875.2 m 2  g −1 ) and highly dispersed AgNPs exhibited adsorption properties and excellent catalytic activities for catalytic reduction of ecotoxic 4-nitrophenol (4-NP) to 4-Aminophenol (4-AP) under visible light. The adsorption of 4-NP was fast since equilibrium was reached in 40 min. The kinetic data were fitted well to the pseudo-second-order kinetic model. The results reveal that within 40 min 98% of 4-NP was successful reduced in to 4-AP suggesting an active catalyst. The post characterization results revealed that no chemical and physical changes were observed after seven successive cycles of the Ag/N–C nanocomposite. This work offers an indication of the future direction of synthesis of nanomaterials which could be adsorbed and treatment of the ecotoxic pollutants. Graphical abstract: Image 1 Highlights: AgNPs embedded into N-doped was fabricated using chitosan. The Ag/N–C nanocomposite showed the high rates of adsorption for 4-nitrophenol. The Ag/N–C nanocomposite showed the catalytic reduction of 4-nitrophenol. The post characterization revealed that no changes in the Ag/N–C nanocomposite.